Transition Metal Complexes of Heptadentate Bipyridine-Based Ligands - Alka Rani (Auckland University of Technology, 2026)
This thesis investigates the coordination behaviour of first-row transition metal ions with novel heptadentate bipyridine-based ligands, focusing on the synthesis, characterization, and complexation properties of two new ligands N-([2,2’-bipydridin]-6-ylmethyl-N’-(2-(([2,2’-bipyridine]-6-ylmethyl)amino)ethyl)ethane-1,2-diamine (bmdet) and N-([2,2'-bipydridin]-6-ylmethyl-N'-(3-(([2,2’-bipyridine]-6-ylmethyl)amino)propyl)propane-1,3-diamine (bmdpt). The ligands were synthesized via reductive amination of 2,2’-bipyridine-6-carbaldehyde with diethylenetriamine (bmdet) and dipropylenetriamine (bmdpt) respectively, and characterized by NMR spectroscopy and high-resolution mass spectrometry, confirming their structures and purity. Cobalt(III) complexes of these ligands were prepared using Na3[Co(CO3)3].3H2O as the precursor. The X-ray crystal structure of [Co2(Hbmdet)2Cl2](ClO4)6 confirmed the dimeric nature of this species, with two six-coordinate Co(III) centres bridged by the heptadentate ligands, with one donor atom of the ligand remaining unbound and protonated. Two chloride ions are bound within cavities formed by the aliphatic and bipyridine parts of the heptadentate ligands. Mass spectrometric studies of complexes of bmdet and bmdpt with Cu2+, Mn2+, Fe2+, Co2+, Ni2+, and Zn2+ demonstrated predominantly mononuclear species in solution. These analyses revealed peaks consistent with 1:1 metal-to-ligand complexes, often showing doubly charged ions corresponding to [M(bmdet)]2+ or [M(bmdpt)]2+ species. Notably, the mass spectra also indicated the presence of ligand-related species, including partially reduced or alternative ligand forms (e.g., L1), which influenced the observed complex distributions. For some metals, such as Mn and Cu, additional peaks suggested equilibrium mixtures involving free ligand, protonated ligand, and metal complexes with varying stoichiometries. Job plot analyses for Cu²⁺ and Co²⁺ with both ligands in acetonitrile revealed differing predominant stoichiometries: Cu²⁺ complexes exhibited a metal-to-ligand ratio near 2:3, implying possible multinuclear or helical assemblies, whereas Co²⁺ complexes favored a 1:1 stoichiometry consistent with mononuclear species. Overall, the combined crystallographic and mass spectrometric data indicate that while heptadentate ligands like bmdet and bmdpt are capable of forming stable complexes with first-row transition metals, complete coordination of all seven donor atoms to a single metal centre is generally precluded. Instead, coordination involves six donor atoms, with the seventh often uncoordinated or facilitating the formation of multinuclear assemblies. These findings provide new insights into the design and binding modes of high-denticity ligands with first-row transition metals, expanding the understanding of coordination chemistry at the upper limits of ligand denticity and highlighting the complex equilibria present in solution.